Energy generation from fish-processing waste using microbial fuel cells - Abdul Syukor, Abd Razak; Suryati, Sulaiman; Chandrakant, Jadhav Pramod; Mishra, Puranjan; Mohd, Nasrullah; Singh, Lakhveer; Zularisam, Abdul Wahid (Elsevier, 2020)
Waste from fish-processing units have been customarily disposed of through dumping at landfill sites or water bodies. Disposing of fish waste can be considered unbefitting waste management practice because the fish waste represents a valuable source of nutrient and energy. This chapter aims to summarize the microbial fuel cell approaches used for the treatment of fish waste. The Malaysian National Green Technology Policy on fish-waste treatment and the characteristics of fish-processing wastewater, along with the physiochemical parameters that affect the treatment process, are discussed in this chapter.